(untitled) (International Journal of Applied Research in Management and Economics, 2025)
The rapid rise of e-government has transformed public sector operations, enhancing efficiency, transparency, and citizen-centered service delivery. This article examines e-government implementation within the Ministry of Justice, using organizational change theories to assess how digital transformation reshapes traditional administrative structures. Focusing on digital case management, online legal services, and reengineered judicial processes, the study explores efforts to improve accessibility and reduce bureaucratic burdens in a highly formalized environment. It also identifies key challenges, including rigid hierarchies, technological limitations, and resistance to change. Despite notable progress in expanding access to justice and streamlining operations, issues such as bureaucratic inertia, data privacy, and the need to balance efficiency with fairness persist. The article concludes with actionable recommendations for policymakers and public managers, emphasizing inclusive change strategies, updated legal frameworks, and continued digital investment. This research contributes to the broader discourse on digital governance by offering insights into inter-organizational collaboration and the distinct challenges of justice sector reforms.